Phylogenetic Trees and Molecular Evolution A Hands-on Introduction with Uncertainty Quantification Corrected - Bickel, David R. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book serves as a brief introduction to phylogenetic trees and molecular evolution for biologists and biology students. It does so by presenting the main concepts in a variety of ways: first visually, then in a history, next in a dice game, and finally in simple equations. The content is primarily designed to introduce upper-level undergraduate and graduate students of biology to phylogenetic tree reconstruction and the underlying models of molecular evolution. A unique feature also of interest to experienced researchers is the emphasis on simple ways to quantify the uncertainty in the results more fully than is possible with standard methods.
Introduction to phylogenetic trees -- A divergence time story: the rise and fall of the molecular clock -- Estimating phylogenetic trees -- Estimating divergence times -- Estimating common ancestors -- Testing theories of molecular evolution -- Recommendations for further reading -- Appendix A: Intermittent point processes -- Appendix B: Poisson processes with Lévy-stable substitution rates.
Keywords: Phylogeny; Biology-Technique.; Gene expression; Bioinformatics; Phylogenetics; Gene Expression Analysis; Bioinformatics